Quality norms for aquaculture products: Trends on restriction problems - Lima dos Santos C.A. (Marketing of aquaculture products, 1996)
The international trade of aquaculture products has been an established practice since last century to increase food production and income. It is recommended that the existing situation should be corrected through adherence to international and national codes of practice. Many of the issues related to the food product safety and quality of the results of aquaculture are covered by the existing FAO/WHO Internationally Recommended Codex Standards and codes of Practices for Fish and Fishery Products. In addition, a number of other codex committees have relevant issues under active consideration. These include the Codex Committees on Food Hygiene, Pesticide Residues, Food Additives and Veterinary Drug Residues. A Draft code of Hygiene Practice for the Products of Aquaculture was prepared by FAO and is presently under review aiming at including HACCP (Hazard analysis and critical control point) principles into the document. This paper presents a review of international and national efforts concerning the regulation of quality and safety aspects for the production and trade of aquaculture products for human consumption.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)